Phylogeny and taxonomic revision of the subgenus Velleius Leach (Coleoptera: Staphylinidae: Staphylininae) - Zhao, Zong-Yi; Zhou, Hong-Zhang (Zootaxa, 2015)
The subgenus Velleius Leach, 1819 of the genus Quedius Stephens, 1829 is a small and very distinctive group in the subtribe Quediina (Staphylinidae: Staphylininae) with pectinate antennal segments and larvae living in nests of Vespa species. This paper reviews the taxonomy of all Velleius species and analyzes the phylogeny of this group. Two new species, Quedius (Velleius) sagittalis sp. nov. from Shaanxi, China and Q. (V.) rectilatus sp. nov. from Guangdong, China, are described. Q. (V.) simillimus (Fairmaire,1891) syn. nov. is proposed as a new synonym of Q. (V.) pectinatus (Sharp, 1874). Phylogenetic result shows that all nine Velleius species can be divided into two clades and both have strong tree supports of Bremer/Bootstrap/Jackknife values.